Rural marketing : focus on agricultural inputs - Singh, Sukhpal (New Delhi : Vikas, 2004)
Contributed articles with reference to India; felicitation volume for R.N. Singh, b. 1936.
Includes bibliographical references.
Keywords: Marketing -- India; Farm produce -- India -- Marketing; Cooperative marketing of farm produce -- India